2021
DOI: 10.3389/fnut.2021.699620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short- and Long-Term Soy Protein Feeding on Hepatic Cytochrome P450 Expression in Obese Nonalcoholic Fatty Liver Disease Rat Model

Abstract: Obesity can lead to chronic health complications such as nonalcoholic fatty liver disease (NAFLD). NAFLD is characterized by lipid aggregation in the hepatocytes and inflammation of the liver tissue as a consequence that can contribute to the development of cirrhosis and hepatocellular carcinoma (HCC). Previously, we reported that feeding obese Zucker rats with soy protein isolate (SPI) can reduce liver steatosis when compared with a casein (CAS) diet as a control. However, the effects of SPI on cytochrome P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Fatty Zucker rat (fa/fa) is a well-known animal model for the study of genetic obesity and the associated fatty liver disease, becoming obese by 3 weeks of age (29,30). Previously, we used obese Zucker rats and reported that soy protein isolate (SPI), which contains high levels of isoflavones (∼90%), can exert protective properties for the liver against liver steatosis in obese Zucker rats (17)(18)(19)(20)31). Soy protein concentrate (SPC) contains lower levels of isoflavones (∼70%) than SPI.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty Zucker rat (fa/fa) is a well-known animal model for the study of genetic obesity and the associated fatty liver disease, becoming obese by 3 weeks of age (29,30). Previously, we used obese Zucker rats and reported that soy protein isolate (SPI), which contains high levels of isoflavones (∼90%), can exert protective properties for the liver against liver steatosis in obese Zucker rats (17)(18)(19)(20)31). Soy protein concentrate (SPC) contains lower levels of isoflavones (∼70%) than SPI.…”
Section: Discussionmentioning
confidence: 99%